First Sight: ESP and Parapsychology in Everyday Life by James C. Carpenter - Pasciuti, Frank (Journal of Scientific Exploration, 2014)
<!--[if gte mso 9]> 14.00 <![endif]-->In First Sight Jim Carpenter presents a model and a set of theoretical ideas about psi. The model offers a new understanding of what psi is. It proposes that psi is carried out continuously and almost entirely unconsciously. According to Carpenter, “Everyone swims in an extrasensory sea, but accesses it and responds to it differently depending on unconscious intention.” A board-certified clinical psychologist with more than 40 years of active experience as a psychotherapist, educator, and researcher, Carpenter’s involvement in parapsychology began in the mid-1960s when he became associated with the Duke Parapsychology Laboratory. After conducting extensive research in parapsychology from the perspective of a clinical psychologist, it’s not surprising that Carpenter believes that “parapsychology belongs to general psychology.” Unfortunately, most contemporary psychologists don’t share that perspective. But I believe that Carpenter’s elucidation of psi’s functioning in terms of long-established psychological constructs, such as cognitive and dynamic psychology, will not only further demystify the mechanisms of psi, but build a traversable bridge to conventional psychological thinking. Carpenter makes the point very early in this book, however, that it’s not his intention to debate the reality or validity of psi. Rather, he operates on a proposition similar to other well-respected psi researchers such as Dean Radin. Their position is that the evidence for psi phenomena is sufficiently established, and that psi research today is less concerned with experiments that prove psi than with questions such as: What influences psi performance? and How does it work? <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->